THE TEACHING AND LEARNING OF WRITING IN INDONESIAN: A CASE STUDY OF A PRIMARY SCHOOL - Tans Feliks; Agustinus Semiun; Hilda M Nalley (Postgraduate School, Universitas Nusa Cendana, 2019)
This case study is about the teaching of writing in an Indonesian state primary school, that is, in Kupang, East Nusa Tenggara Province. It aims at finding out: 1) how writing in Indonesian is taught in the research school; 2) how competent the students are in writing in Indonesian as the results of their teachers’ teaching of writing in Indonesian; 3) proper teaching teachniques done in order to better the athmosphere of the teaching and learning of writing in the research school. The method used was a case study with the school as a research object and the teachers teaching Indonesian writing in the school and their students from grade I to grade VI learning to write in Indonesian as reseach subjects. This study was done from July to November 2017. The data collected through interviews, observations, and documentary studies were analyzed descriptively. It was found that the teaching and learning of writing in the school was traditionally done, that is, it was not to improve students’ writing in Indonesian, but to improve other skills like reading, speaking, and listening. Despite such a traditional method in the teaching and learning of writing in Indonesian, it was found that the students could write generally well in Indonesian. The teachers in the school believe that they need to do some changes in order to ensure that their students can write well in Indonesian like: “joining more courses/trainings on the teaching and learning of writing for publication;” continuing their formal study/degree; providing more teaching facilities so that it is much easier for them to teach writing, to revise, to edit, and to publish their students’ writings; and, working hand in hand with fellow teachers to improve their students’ writing competence.